Handbook of research on innovations in Technology and Marketing for the Connected Consumer - Dadwal, Sumesh Singh (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
Connected customers, using a wide range of devices such as smart phones, tablets, and laptops have ushered in a new era of consumerism. Now more than ever, this change has prodded marketing departments to work with their various IT departments and technologists to expand consumers' access to content. In order to remain competitive, marketers must integrate marketing campaigns across these different devices and become proficient in using technology. The Handbook of Research on Innovations in Technology and Marketing for the Connected Consumer is a pivotal reference source that develops new insi.